NEAT1 Negatively Regulates Cell Proliferation and Migration of Neuroblastoma Cells by miR-183-5p/FOXP1 Via the ERK/AKT Pathway. (20th July 2020) - Pan, Weikang; Wu, Ali; Yu, Hui; Yu, Qiang; Zheng, Baijun; Yang, Weili; Tian, Donghao; Gao, Ya; Li, Peng
Neuroblastoma, a malignant tumor of the sympathetic nervous system, is an aggressive extracranial tumor in childhood. Long noncoding RNAs (lncRNAs) have been discovered to play a key role in the eukaryotic regulatory gene network and be involved in a wide variety of biological processes. We observed that the expression of lncRNA nuclear-enriched abundant transcript-1 (NEAT1) was significantly decreased in human neuroblastoma tissues and cell lines, compared with the normal. We observed cell proliferation, migration, and invasion with Cell Counting Kit-8 assay, colony formation assay, and Transwell assay to investigate the effects of NEAT1, miR-183-5p, or FOXP1 on neuroblastoma cells. And we also used StarBase and luciferase reporter gene assay to predict and confirm the interaction of NEAT1, miR-183-5p, and FOXP1 in neuroblastoma cells. First, overexpression of NEAT1 suppressed cell proliferation and played a key role in cell migration and invasion. In addition, NEAT1 was demonstrated to directly interact with miR-183-5p and exerted its antioncogenic role in neuroblastoma by negatively regulating miR-183-5p expression. miR-183-5p suppressed the expression of FOXP1 and regulated cell proliferation and migration by directly targeting FOXP1 mRNA 3′-untranslated region. Moreover, FOXP1 antagonized the effect of miR-183-5p on the phosphorylation of extracellular-regulated kinase/protein kinase B (ERK/AKT), while FOXP1 siRNA increased the reduced phosphorylation of ERK/AKT caused by miR-183-5p inhibitor in neuroblastoma cells. Taken together, these data showed that NEAT1 negatively regulated cell proliferation and migration of neuroblastoma by the miR-183-5p/FOXP1 axis via suppression of the ERK/AKT pathway. Our findings may provide a new target for the study of pathogenesis and treatment of neuroblastoma.